Breastfeeding maintenance of very low weight premature babies: experience of mothers - Beatriz de Carvalho Ciaciare; Michelle Thais Migoto; Talita Balaminut; Mauren Teresa Grubisich Mendes Tacla; Sarah Nancy Deggau Hegeto de Souza; Edilaine Giovanini Rossetto (Universidade Federal de Goias, 2015)
The objectives of this study were to comprehend the breastfeeding process from reports of mothers of premature babies and identify factors facilitating or complicating this process. A descriptive qualitative study regarding the family centered care. We conducted 12 interviews with mothers of six months premature babies of chronological age and we submitted data to content analysis. Four categories emerged: The previous breastfeeding experience in the process of breastfeeding the premature baby; Emotional context versus the breastfeeding process; The ability to manage breastfeeding the premature baby and, Successes and failures. We concluded that family and professional support, adequate management and the welcoming of individualized services in the prematurity context were majorly responsible for the breastfeeding success, being even able to surpass the previous maternal desire. Breastfeeding accompaniment after discharge is indispensable for its success with premature babies.